The Moon Illusion as (Partly) an Error in Apparent Visual Angle: A New Possibility. (November 2019) - Parks, Theodore E.
An illusory exaggeration of the horizon moon's visual angle (together with an apparently larger physical size) may account for its dramatic appearance.